Knowledge of clear aligner therapy in orthodontics among dental practitioners in Benin city, Nigeria - Otaren NJ (Ibom Medical Journal)
Background: Clear aligners have been used in orthodontics since 1946 when Dr Harold Kesling introduced the use of a series of thermoplastic tooth positioners to obtain tooth alignment.